2007
DOI: 10.1007/s11547-007-0166-0
|View full text |Cite
|
Sign up to set email alerts
|

Cystic adenomatoid malformation in children: CT histopathological correlation

Abstract: In our study, there was concordance between CT and histopathology in 66.7% of cases, whereas in 33.3% histopathology revealed areas with mixed grade lesions. CT proved to be accurate in identifying and characterising CAM and provided important information on lesion site and extension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 17 publications
0
6
0
1
Order By: Relevance
“…Agreement between PUS and histology and MDCT and histology was observed in 76.9 % (20/26) and 94 % (31/33) of the cases, respectively. Overall, the PPV of the survey MDCT scans compared with histology was 93.3 %, compared with a reported value of 70 % in the literature [19]. As most surgeons consider surgical resection of these lesions mandatory, MDCT can provide detailed anatomical localisation of lesions, with the possibility of 3D reconstruction and high spatial resolution.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Agreement between PUS and histology and MDCT and histology was observed in 76.9 % (20/26) and 94 % (31/33) of the cases, respectively. Overall, the PPV of the survey MDCT scans compared with histology was 93.3 %, compared with a reported value of 70 % in the literature [19]. As most surgeons consider surgical resection of these lesions mandatory, MDCT can provide detailed anatomical localisation of lesions, with the possibility of 3D reconstruction and high spatial resolution.…”
Section: Discussionmentioning
confidence: 80%
“…After birth, chest X-ray is no longer the first imaging approach, as it fails to detect lesions in about 60 % of asymptomatic patients [19]. However, in clinical practice, chest X-ray is still used as the first-line approach only for patients with respiratory distress.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis is suggested by CXR, however, a thoracic CT scan is required to confirm the diagnosis [25, 26]. Winters et al reported that CXR features can be subtle in children with disappearing fetal lung masses, hence postnatal CT scan is needed [18].…”
Section: Congenital Pulmonary Airway Malformation (Cpam)mentioning
confidence: 99%
“…Mucus can distend the multiple intercommunicating spaces, making the lesion appear radiologically solid or sonographically hyperechoic unless, as in the case of intralobar sequestration, air penetrates through the pores of Kohn. An increasing number of authors suggest that intralobar sequestration may also derive from recurrent infections that produce anomalous arterial branches from the aorta (such as the pulmonary ligament arteries) [51].…”
Section: Malformazione Adenomatoide Cistica Congenita (Ccam)mentioning
confidence: 99%
“…Il muco può distendere i multipli spazi intercomunicanti, conferendo un aspetto radiologicamente solido alle lesioni o iperecogeno all'ecografia, a meno che, in caso di sequestro intralobare, l'aria vi penetri tramite i pori di Kohn. Un sempre maggiore gruppo di autori ipotizza che il sequestro intralobare possa anche derivare da infezioni ricorrenti che producono rami arteriosi anomali dall'aorta (come le arterie del legamento polmonare) [51].…”
Section: Malformazione Adenomatoide Cistica Congenita (Ccam)unclassified